Yahoo Web Search

  1. Ads
    related to: ABH
  1. V(rectangular prism) = whd = (2x - 6)(x - 3)(4) V(pyramid) = abh = (4)(2x + 1)(x - 5) the volumes are equal, so: 4(2x - 6)(x - 3...

    2 Answers · Science & Mathematics · 07/04/2013

  2. ...the sine rule in triangle BAH HB / sin 60° = 25 / sin θ where θ = angle ABH sin θ = 25 * sin 60° / 31.2 = 0.6934 θ = 43.9° Then θ - 30° = 13.9...

    2 Answers · Science & Mathematics · 09/02/2010

  1. Ads
    related to: ABH
  1. Try asking your question on Yahoo Answers